Soluble plasma programmed death 1 (PD-1) and Tim-3 in primary HIV infection - Frater, J; Martin, GE; Willberg, CB; Zilber, E; Fox, J; Nwokolo, N; Fidler, S; CHERUB Investigators (Lippincott, Williams & Wilkins, 2019)
Soluble forms of the coinhibitory receptors programmed death 1 (PD-1) and Tim-3 exist, but their relationship with T-cell surface expression remains unclear. When measured by an enzyme-linked immunosorbent assay in plasma, soluble PD-1, and soluble Tim-3 were elevated during primary HIV infection, decreased on antiretroviral therapy to levels found in controls, and correlated with cell surface expression. We conclude that soluble PD-1 and soluble Tim-3 are easy to measure biomarkers of immune exhaustion which potentially eliminate the need for flow cytometry.